(untitled) (Research, Society and Development, 2021)
Non-communicable chronic diseases are responsible for great harm to public health in the world, where the premature mortality rate has been showing a great increase. Thus, the objective of this work was to understand the importance of the Nutritionist in the treatment of non-communicable chronic diseases. This is a qualitative cross-sectional study. The research consisted of a sample of 21 nutritionists who carry out nutritional monitoring with patients with chronic non-communicable diseases. Data collection took place through an online Google form and were analyzed using a simple average in the Excel 2018 program. A predominance of high rates for diabetes (90.5%) and hypertension (85.7%) and obesity was identified (95.2%) in patients. It was observed that behavioral aspects (76.2%) and income (57.1%) were determinants of inadequate food intake. The research showed a high intake of processed (66.7%) and ultra-processed (57.1%) foods. The prevention and control of CNCDs and their risk factors are essential to avoid an epidemic growth of these diseases and their consequences for the quality of life and the health system in the country. Therefore, the action of the nutritionist, with the help of documents such as the Food Guide for the Brazilian Population, is of paramount importance for adherence to an adequate and healthy diet.